Abuse of rights - Danielyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2021)
In this article, the author has comprehensively studied the theoretical-practical questions related to the term «abuse of rights». At the same time, in order to ensure the completeness of the analysis, this term was considered in the context of other similar terms, such as «abuse of authority», «abuse of position», etc.The article underlines the conclusion that the term «abuse of law» should be used only in cases when its specific content is revealed as a type of offense. At the same time, in the context of exercising procedural rights, the position was substantiated that the practice of imposing an unnecessarily high state duty in order to exclude the abuse of the mentioned rights could not be considered lawful. The author also referred to the discovery of new aspects of the term «abuse of power». For that purpose was analyzed the special legal regimes established by the Government during 2020 and the policy towards them in practice.Based on the results of the analysis, the author has proposed a number of other systematic conclusions, which may be useful from the point of using the above-mentioned terms more purposefully, in general, to have a starting point in the process of including the terms of public discourse in jurisprudence.
Keywords: abuse of rights; abuse of obligation; conscientious behavior; abuse of authority; offense; restriction of rights; purpose of the legislator